When to Brush Teeth after Single Short Time Intake of Carbonated Soft Drink to Prevent Enamel Abrasion? - Koji Watanabe; Shigeru Watanabe; Kenshi Maki (Highlights on Medicine and Medical Research Vol. 1, 2021)
The aim of this chapter was to evaluate amount of calcium elution from bovine enamel due to single and short immersion into carbonated soft drink, to calculate depth of the eroded lesion, and to determine when to brush teeth after carbonated soft drink intake from the view point of preventing enamel abrasion. Four enamel specimens (4 mm width × 4 mm height × 5 mm thickness) were cut out of each bovine crown (a total of 8 bovine crowns were used), followed by making enamel samples by embedding them in quick cure resin. The enamel samples in each crown were randomly divided into 3 minutes of immersion (IM3), 6 minutes of immersion (IM6), 9 minutes of immersion (IM9), and 12 minutes of immersion (IM12) groups, and then, immersed in 5 mL of carbonated soft drink for respective immersion time. The amount of eluted calcium per unit area of the enamel surface was measured using atomic absorption spectrophotometry, and then, the depth of the demineralized lesion was calculated. Both the amount of eluted calcium and the lesion depth in the IM6, IM9, and IM12 groups was significantly higher than that in the IM3 group. Even in the IM12 group, the lesion depth ranged 0.05-0.35 µm. A white spot lesion that is remineralized by oral fluid was reported to range 50 - 600 µm, so the eroded lesion depth in this study was considered to be remineralized by saliva quickly, hence it was concluded that brushing just after single short time intake of carbonated soft drink hardly induce enamel abrasion.